Lipase-mediated degradation of poly-ɛ- caprolactone in toluene: Behavior and its action mechanism / Muhammad Haziq Aris - Muhammad Haziq , Aris (2017)
Poly-ɛ-caprolactone (PCL) is a semi-crystalline polyester, hydrophobic in nature and highly degradable. However, these properties make it unsuitable for many applications. Blending of PCL oligomers with other polymer(s) helps to improve its characteristics. It is suggested that by degrading the long PCL chain into moderate length would permit the blending and functionalization processes to be more amenable to control variables. In this study, lipase-catalyzed hydrolysis of PCL in toulene was investigated. PCL with number-average molecular weight (Mn) 10,000 g mol-1 was hydrolyzed using immobilized Candida antarctica lipase B (CALB). The increase in PCL concentration led to a decrease in degradation rate. Enhanced rate was observed when reaction temperature was increased from 30 to 50 °C. Enzymatic chain scission of PCL yielded cyclic dicaprolactone, tricaprolactone, tetracaprolactone and oligomers with Mn less than ~ 1000 g mol-1. Catalytic formation of cyclic lactones via back-biting mechanism in low water content environment was attributed to CALB. Its hydrolysis of PCL displayed consecutive random- and chain-end scission with time from detailed thermal, molecular weight and structural analyses. Apparent activation energy, Ea for hydrolysis was 45 kJ mol-1 i.e. half of that reverse reaction. Dicaprolactone and oligomers from hydrolysis readily re-polymerized to produce mid-range polymer with Mn 1400 g mol-1 after 36 hours in the same reaction medium. These versatile oligomers can be applied as integral components for processes such as copolymerization or functionalization of valuable compounds.